2013
DOI: 10.1016/j.ccr.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Irradiation Programs Macrophage Differentiation to an iNOS+/M1 Phenotype that Orchestrates Effective T Cell Immunotherapy

Abstract: Inefficient T cell migration is a major limitation of cancer immunotherapy. Targeted activation of the tumor microenvironment may overcome this barrier. We demonstrate that neoadjuvant local low-dose gamma irradiation (LDI) causes normalization of aberrant vasculature and efficient recruitment of tumor-specific T cells in human pancreatic carcinomas and T-cell-mediated tumor rejection and prolonged survival in otherwise immune refractory spontaneous and xenotransplant mouse tumor models. LDI (local or pre-adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
719
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 887 publications
(748 citation statements)
references
References 36 publications
26
719
2
1
Order By: Relevance
“…In addition to their large number, macrophages have the ability to support vascular normalization, improve T cell recruitment and promote Th1 responses after differentiation into M1 phenotype. 22 Here, we further tested whether macrophages were required for the combined treatment of CisMPs and LDI. To this end, we used clodronate liposomes, a wide used approach, to deplete macrophages.…”
Section: Combination Of Cis-mps and Ldi Generates Better Tumor Treatmmentioning
confidence: 99%
“…In addition to their large number, macrophages have the ability to support vascular normalization, improve T cell recruitment and promote Th1 responses after differentiation into M1 phenotype. 22 Here, we further tested whether macrophages were required for the combined treatment of CisMPs and LDI. To this end, we used clodronate liposomes, a wide used approach, to deplete macrophages.…”
Section: Combination Of Cis-mps and Ldi Generates Better Tumor Treatmmentioning
confidence: 99%
“…The possible mechanisms undergirding these findings are that radiotherapy upregulates tumor-associated antigen-MHC complexes, enhances antigen cross-presentation in the draining lymph node, boosts T cell infiltration into tumors, 42 and promotes tumor-associated macrophage transformation from M2 to M1. 43 At the same time, emerging evidences indicated that low doses of fractionated radiotherapy led to PD-L1 upregulation on tumor cells by recruiting infiltrated lymphocytes in an IFNg-dependent manner, and fractionated radiotherapy delivered in combination with anti PD-1 or anti PD-L1 mAbs generated efficacious CD8 C T-cell responses that improved local tumor control, long-term survival, and protection against tumor re-challenge. 44,45 Although we showed that the PD-1-disrupted LMP2A-CTLs conferred enhanced cytotoxicity to the EBV-positive gastric cancer cell line in vitro, in the xenograft model of EBVaGC, we did not observe augmented tumor regression following treatment of PD-1 disrupted LMP2A-CTL.…”
Section: E1249558-10mentioning
confidence: 99%
“…However, recent studies in the tumor stroma showed that high doses of IR (> 8Gy) promote anti-inflammatory activation of macrophages, 20 and low doses (< 2Gy) combined with immunotherapy induce proinflammatory activation of macrophages that favor tumor elimination. 21 These data suggest that there is a direct effect of IR on macrophage activation. Upon activation, macrophages produce bystander signals 9 and play an important role in the development of radiation injury.…”
Section: Macrophage Response To Radiotherapymentioning
confidence: 89%
“…In tumor models, macrophage reprograming using a low dose of IR resulted in an antitumor activity. 21 Accordingly, in IR-induced tissue toxicity, the use of a proinflammatory agent could be a potential strategy to reprogram macrophage polarization and switch the profibrotic profile of macrophages to a more proinflammatory, antifibrotic one.…”
Section: Macrophages Involvement In Radiation-induced Injurymentioning
confidence: 99%